2017
DOI: 10.1111/jch.13102
|View full text |Cite
|
Sign up to set email alerts
|

Traffic congestion and blood pressure elevation: A comparative cross‐sectional study in Lebanon

Abstract: This comparative cross‐sectional study examines the association between traffic congestion and elevation of systolic and/or diastolic blood pressure levels among a convenience sample of 310 drivers. Data collection took place during a gas station pause at a fixed time of day. Higher average systolic (142 vs 123 mm Hg) and diastolic (87 vs 78 mm Hg) blood pressures were detected among drivers exposed to traffic congestion compared with those who were not exposed (P<.001), while controlling for body mass index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We focused on these individuals to control other possible travel-mode related factors that may also influence how traffic congestion exposure affects health. For instance, previous studies found that the effects of traffic congestion exposure on health may be different when individuals are drivers rather than passengers (e.g., [41,42]). Moreover, they found that the existence of accompanied passengers may affect drivers’ stress (e.g., [7,42,43]).…”
Section: Study Area and Datamentioning
confidence: 99%
“…We focused on these individuals to control other possible travel-mode related factors that may also influence how traffic congestion exposure affects health. For instance, previous studies found that the effects of traffic congestion exposure on health may be different when individuals are drivers rather than passengers (e.g., [41,42]). Moreover, they found that the existence of accompanied passengers may affect drivers’ stress (e.g., [7,42,43]).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Another paper [5] showed by experiments that the heart rate increases when associating driving with other activities or cognitive workload that requires much attention, observation, and mental effort. In addition, the authors of [6] analysed in their work the impact of exposure to traffic congestion on the blood pressure of the driver, and they noticed that longer exposure time was associated with higher systolic and diastolic blood pressure levels since traffic congestion might trigger an inconvenient atmosphere which can be associated with anger, stress, or frustration that cause an increase in the blood pressure levels. These findings suggest that a driver's behaviour and the external factors during driving can have a notable impact on physiological indicators.…”
Section: Motivationmentioning
confidence: 99%
“…Proactive measures must be taken to ensure that drivers maintain safe driving practices and remain mindful of the ways in which external factors can affect their driving behaviour and other vital signs. To this end, many studies have been undertaken to observe and investigate the influence of external factors and driving behaviour on vital signs such as heart rate and blood pressure [2,5,6]. However, these investigations have often been limited by their narrow focus on events either inside or outside the vehicle, as well as by the use of cumbersome devices to observe a single vital sign in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Congestion in the streets can have a negative impact on people's psyches (Ganesh, 2019). Studies show that the stress and high blood pressure that people experience in heavy traffic have a lasting effect on their health (Bou Samra et al, 2017). Therefore, it's crucial to learn why people dislike using public satisfaction and experience of commuters using public transport in the city.…”
Section: Ktm Serves the Outlying Areas Of Greater Kualamentioning
confidence: 99%